THE CONTENT AND STRUCTURE OF PROFESSIONAL PSYCHOLOGICAL COMPETENCE OF FUTURE TEACHERS - Savrasova-V’un Tatiana А. (Educological discourse, 2015)
The article investigates the determination of the content and structure of professional psychological competence of future teachers. Characterized by basic scientific research approaches professional psychological competence of future professionals. A content analysis of the concept of «professional psychological competence of future teachers». The main components of the structure and performance professional psychological competence of future teachers.